The Design of Antenatal Care Visit Behavior of Pregnant Women in Public Health Center of Jember Regency - Zakdiyah, Lailatuz; Hernawati, Sri; Yani, Ristya Widi Endah (Health Notions, 2018)
Antenatal care service is a health service which is carried out by medical staffs to pregnant women while pregnancy period is based on the minimum service standards. Antenatal care examinations are very important for womens pregnancy health from first trimester to the childbirth. The purpose of this research was to examine the determinants of the antenatal care behavior of pregnant women in the work area of ââthe Kalisat Public Health Center. The respondent 77 people were taken by proportionate stratified random sampling. The instrument used was check list of knowledge, behavior, family support, cadre support, health officer support. The result of logistic regression test showed that there were influence of determinan factors on antenatalcare behavior of pregnant at public health center. Keywords: Antenatal care, Health behavior, Pregnant women